Identity and performance in technical Q&A. - Vargo, Andrew W.; Matsubara, Shigeo (Behaviour & Information Technology, 2018)
Identity and the different roles identities play in social question-answering communities have long been discussed from both a theoretical and empirical standpoint. Identity is usually analysed in ways that emphasise a transaction, and many studies use third-party raters to assign value judgements to these factors, which may not be relevant to a community. In this article, we examine identity in Stack Overflow, a question and answer site dedicated to solving computer-programming problems, which has a competitive community run reputation system. Profiles on Stack Overflow are highly customizable, allowing users to choose the level of personal information they want to share: from extensive to none. We develop a categorisation scheme using grounded theory to develop definitions of identity, and analyse behaviour based on these definitions. We find that the choice of identity is diverse within the community and that there is a correlation with identifiers and increased reputation earning among the general population. An analysis of elite users, however, indicates that identity is closely tied to membership length, but not to performance. The results indicate that allowing identity choices does affect system efficacy or user outcomes.